Factors Influencing Patient Satisfaction With Pain Management Among Post Caesarean Section Patients In The Greater Accra Regional Hospital, Ghana - Wiafe, D.O. (University of Ghana., 2019)
Background: The rate of cesarean sections is on the rise and being performed more frequently in recent times. Pain is a major problem in post--operation recovery and a known cause for acute pain in obstetrics; its relief and patient satisfaction are still inadequate in many cases. Objective: This study examined factors influencing patient satisfaction with pain management post – cesarean delivery at the Greater Accra Regional Hospital. Method: A descriptive cross·sectional study design was employed and quantitative methods used to collect data. A semi structured close and an open-ended questionnaire were used to collect data on women who had undergone ceasearen section(c/s) at the Greater Accra Regional Hospital. STATA 15 was used to perform both descriptive and inferential statistical analysis Results: The study results show that the level of pain experienced within 24 hours post - ceasearan section was moderate 40.40% and severe 58.9% respectively. Slightly more than half S2.2% of patients had elective CIS and 47.8% had emergency CIS. Majority; 85.9 percent of the post-C/S patients were satisfied with the pain management given them. Determining factors that influenced patient's satisfaction with pain managements, this study results indicates that patients who have singletons are 2.81 times more likely to be satisfied with pain management as compared to those who had twin deliveries [AOR=2.81 (95% CI: 1.14-6.92); p=0.023]. Patients who were aged 30-39 were 70% less likely to be satisfied with pain management as compared to those aged <30 years [AOR=0.30 (95% CI: 0.10-0.92); p=0.032]. Conclusion: Most mothers, 99.3%, had moderate to severe pain 24hours after C/S. Also 85.9 percent of the post-C/S mothers were satisfied with the pain management given them. The findings of this study indicated that the age of the mother influenced their satisfaction with pain management. Mother who had singletons were more likely to be satisfied with their pain management.
MPH Degree
Keywords: Patient Satisfaction; Pain Management; Post Caesarean Section Patients; Ghana